Mechanism of action of nadofaragene firadenovec-vncg - Narayan, Vikram M.; Meeks, Joshua J.; Jakobsen, Jørn S.; Shore, Neal D.; Sant, Grannum R.; Konety, Badrinath R. (Frontiers in Oncology, 2024)
Effective bladder-preserving therapeutic options are needed for patients with bacillus Calmette-Guérin unresponsive non–muscle-invasive bladder cancer. Nadofaragene firadenovec-vncg (Adstiladrin®) was approved by the US Food and Drug Administration as the first gene therapy in urology and the first intravesical gene therapy indicated for the treatment of adult patients with high-risk bacillus Calmette-Guérin–unresponsive non–muscle-invasive bladder cancer with carcinoma in situ with or without papillary tumors. The proposed mechanism of action underlying nadofaragene firadenovec efficacy is likely due to the pleiotropic nature of interferon-α and its direct and indirect antitumor activities. Direct activities include cell death and the mediation of an antiangiogenic effect, and indirect activities are those initiated through immunomodulation of the innate and adaptive immune responses. The sustained expression of interferon-α that results from this treatment modality contributes to a durable response. This review provides insight into potential mechanisms of action underlying nadofaragene firadenovec efficacy.